(untitled) (International Seven Journal of Health Research, 2023)
Neonatal Lupus Erythematosus (ENL) is a rare autoimmune disease in which immunoglobulin G is transported across the placenta into the fetal circulation. It affects both males and females. The most common clinical manifestations have been found to be skin changes, hematologic changes, hepatobiliary changes and cardiac involvement such as atrioventricular block. However, some of these symptoms tend to disappear naturally after a few months. The diagnosis can be made by biopsy, which will show histopathological mechanisms similar to those of discoid lupus and direct immunofluorescence will show the presence of IgG at the dermal-epidermal junction. The aim of this article was to improve knowledge through an integrative literature review, which used a synthesis of results obtained through research already published in order to make argumentation of the results found. It was found that the use of sunscreen, healthy habits and lifestyle and palliative treatment when applied properly, can control and even make the symptoms of this disease disappear.